Drivers for Geostationary 2–200 keV Electron Fluxes as Observed at GOES Satellites - M. van deKamp; N. Ganushkina; L. Simms; M. Liemohn (Space Weather)
Abstract Electron fluxes in the keV energy range can cause significant spacecraft surface charging, which in turn can affect the functioning of spacecraft components. In this paper, the geostationary electron fluxes measured by the satellites GOES 13‐18 in the energy range 2–200 keV are analyzed in order to look for their dependence on solar wind conditions. For this purpose, a range of solar wind parameters, IMF parameters and geomagnetic indices are examined, to look for the parameters which most significantly affect the electron flux. The analysis includes fluxes in the lower energy range of 2–40 keV, measured by GOES 16‐18, which have not been analyzed before. The measured electron fluxes are averaged over all directions, and high‐pass filtered to isolate variations shorter than 1 month. The analysis concentrates of the dawn sector, where variations are largest. A number of solar wind parameters and magnetic indices are analyzed concurrently with the electron flux data, to look for the most significant correlations between them. Most parameters have the highest correlation with electron flux when shifted in time by a certain delay. In addition to the different solar wind parameters and magnetic indices, combinations of different parameters are also examined for their best correlation with the electron flux. The most significant driving parameters are found to be the auroral electrojet index, combined with either the solar wind plasma velocity or the plasma density. The relative contribution of each of these parameters depends on electron energy, and differs between periods of high and low flux.